Are hyper-growth firms inherently different? Preliminary evidence from a sample of fast-growing European SMEs. (2017) - Minola, Tommaso; Cogliati, Giordano Maria; Cassia, Lucio; Paleari, Stefano
Examples of extremely high-growth firms are receiving increasing attention from researchers and policymakers, as they account for the majority of new job generation and contribute to wealth and general economic development. In particular, recent research has focused on hyper-growth firms, meaning firms that rapidly grow to hundreds of times their original size. However, although it is easy to conceive that such firms are different from the 'usual' high-growth firms, literature has mostly overlooked hyper-growth as a different phenomenon with its own distinctive characteristics. This study tries to fill this gap by focusing on the factors distinguishing a sample of 307 European hyper-growth SMEs from a matched sample of high-growth counterparts. Hyper-growth firms emerge as younger, show greater involvement in M&A and listing activities, and rely more (in relative terms) upon investments in fixed assets financed with high levels of debt. They are also more likely to result from corporate venturing activities and make use of slack resources as a driver of opportunity exploration. Our preliminary evidence suggests that hyper-growth firms may be inherently entrepreneurial. This opens avenues for future research, and these are discussed together with the managerial and policy implications.